Detrimental Changes in Individual Health-Promoting Behaviors Among Internally Displaced Israelis - Naomi Fliss Isakov; Naomi Fliss Isakov; Miri Levi-Shahar; Yulia Balmakov; Ranaa Mahajni Yunis; Ronit Endevelt; Ronit Endevelt; Moran Blaychfeld Magnazi (International Journal of Public Health)
ObjectivesIsrael has forcibly displaced more than 200,000 people to hotels or apartments, due to armed conflict. Our study aimed to identify changes in health-promoting behaviors during displacement.MethodsTwo online surveys were conducted assessing health-promoting behaviors and body weight before and during displacement. Univariate and multivariate analyses were performed to compare displaced and non-displaced respondents.ResultsA total of 997 and 153 participants completed the first and second surveys respectively. A significant decrease in diet quality (P < 0.001), physical activity frequency (P = 0.016), and an increase in diet quantity (P < 0.001) and weight (P = 0.001) were reported among displaced individuals, compared to non-displaced individuals. Living with children, and a healthy pre-war lifestyle were found to be independently protective of detrimental lifestyle change (OR = 0.46, 95% CI0.28–0.76 and OR = 0.63, 95% CI0.40–0.97), risk factors (OR = 2.40, 95% CI1.30–4.43 and OR = 3.54, 95% CI1.71–7.32), for detrimental lifestyle changes.ConclusionDetrimental changes to health promoting behaviors were reported in all study groups, although they were significantly higher in displaced individuals. Immediate changes did not differ between respondents staying in hotels or apartments, but were sustained only in hotels.